2004
DOI: 10.1007/s00415-004-0461-9
|View full text |Cite
|
Sign up to set email alerts
|

Cognitive changes in patients with Huntington?s disease (HD) and asymptomatic carriers of the HD mutation

Abstract: Tasks measuring mainly attention, object and space perception and executive functions adequately assess the progression of HD disease. Other cognitive functions do not significantly deteriorate. Furthermore, problems in attention, working memory, verbal learning, verbal long-term memory and learning of random associations are the earliest cognitive manifestations in AC.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

16
162
1
7

Year Published

2007
2007
2019
2019

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 236 publications
(189 citation statements)
references
References 60 publications
16
162
1
7
Order By: Relevance
“…These findings replicate similar previous results (Berrios et al, 2002;Campodonico et al, 1998;Hahn-Barma et al, 1998;Lemiere et al, 2004), but are in contrast to others (de Boo et al, 1999;Giordani et al, 1995;Rothlind et al, 1993;Strauss & Brandt, 1990). Given that effect sizes were small in the CL0 group and medium in the CL1 group, previous null findings may well reflect inadequate power to detect these subtle effects, especially in samples that include only individuals with a near or total absence of motor signs or who are very far from estimated age of onset.…”
Section: Discussionsupporting
confidence: 89%
See 1 more Smart Citation
“…These findings replicate similar previous results (Berrios et al, 2002;Campodonico et al, 1998;Hahn-Barma et al, 1998;Lemiere et al, 2004), but are in contrast to others (de Boo et al, 1999;Giordani et al, 1995;Rothlind et al, 1993;Strauss & Brandt, 1990). Given that effect sizes were small in the CL0 group and medium in the CL1 group, previous null findings may well reflect inadequate power to detect these subtle effects, especially in samples that include only individuals with a near or total absence of motor signs or who are very far from estimated age of onset.…”
Section: Discussionsupporting
confidence: 89%
“…Similarly, a pre-HD group demonstrated selective impairments in verbal memory on a word list learning task (Lundervold & Reinvang, 1995). In addition, longitudinal data from a sample of pre-HD participants indicates that declines in verbal learning and memory are detectable prior to clinical symptom onset (Lemiere, Decruyenaere, Evers-Kiebooms, Vandenbussche, & Dom, 2004). Specifically, studies of memory in pre-HD have documented significantly poorer performance, relative to non-CAG expanded individuals, on measures of learning (Rosenberg, Sorensen, & Christensen, 1995), semantic clustering (Rosenberg et al, 1995), recall (Hahn-Barma et al, 1998;Rosenberg et al, 1995), and recognition discriminability (Berrios et al, 2002;Lanto, Riege, Mazziotta, Pahl, & Phelps, 1990).…”
Section: Introductionmentioning
confidence: 96%
“…In line with the notion that WM processes are subserved by frontoparietal and striatal areas, WM deficits and frontostriatal dysfunction have also been demonstrated in other disorders of the basal ganglia, e.g., Parkinson's disease [PD] [Altgassen et al, 2007;Lewis et al, 2003;Monchi et al, 2000]. In HD, WM dysfunction is present during early stages of the illness [Lemiere et al, 2004] and has been demonstrated in both patients with manifest HD and individuals with the HD gene mutation who are presymptomatic for the motor symptoms of the disorder [pre-HD individuals] [Lawrence et al, 1996;Montoya et al, 2006;Nehl et al, 2001]. In a sample of pre-HD individuals, we have recently shown aberrant activation of the dorsolateral prefrontal cortex (DLPFC) during WM performance [Wolf et al, 2007b], demonstrating that DLPFC dysfunction may occur several years before the onset of manifest HD symptoms.…”
Section: Introductionmentioning
confidence: 66%
“…We also sought to provide additional information about the studied HD population by using a complementary behavioral assessment of other cognitive domains in addition to verbal WM, including attention, inhibition of prepotent responses, and executive function. As demonstrated by previous studies [Lemiere et al, 2004;Snowden et al, 2001;Ward et al, 2006], we predicted behavioral deficits in HD patients during WM and executive performance. On the functional level, we were particularly interested in the circuitry involving the lateral prefrontal cortex, since impaired prefrontal circuitry has been recognized to play a crucial role in the pathophysiology of the cognitive symptoms found in manifest HD [Montoya et al, 2006;Snowden et al, 2001;Zakzanis, 1998].…”
Section: Introductionmentioning
confidence: 87%
“…Although severe motor impairments characterize the disease, cognitive and memory deficits are also present and often appear in advance of other symptoms (3)(4)(5)(6). Impaired learning that occurs before or concurrent with motor dysfunction or neuron loss has been described for HD mouse models (7)(8)(9) as have deficits in hippocampal long-term potentiation (LTP) (10)(11)(12)(13), a form of synaptic plasticity widely regarded as a neurobiological substrate for memory.…”
mentioning
confidence: 99%